The Role Of Multidisciplinary Team In Implementing Integrated Care Models: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: The role of multidisciplinary teams (MDTs) in integrated care models has gained significant attention due to their potential to improve patient outcomes and healthcare system efficiency. Integrated care, which involves coordinated efforts from professionals across various healthcare disciplines, aims to provide comprehensive care, especially for patients with complex needs. However, challenges related to communication, technology integration, and team dynamics persist, particularly in resource-constrained settings.Aim: This systematic review aims to explore the role of multidisciplinary teams in the implementation of integrated care models, focusing on how these teams contribute to improving patient outcomes, enhancing healthcare delivery, and increasing system efficiency.Method: A comprehensive literature search was conducted across five academic databases—PubMed, Scopus, Web of Science, CINAHL, and Google Scholar—to identify peer-reviewed empirical studies published between 2021 and 2025. Studies that examined integrated care models involving MDTs were included. Data from 15 high-quality studies were synthesized to identify key themes, trends, and findings related to MDT effectiveness in integrated care.Results: The findings revealed that MDTs significantly improve patient outcomes, especially in chronic disease management, mental health, and community-based care. Multidisciplinary teams were associated with better care coordination, enhanced patient satisfaction, and cost savings. However, barriers such as communication challenges, digital health adoption, and lack of infrastructure were identified as critical factors hindering the full implementation of these models.Conclusion: Multidisciplinary teams play a crucial role in the success of integrated care models. While their integration leads to improved healthcare outcomes, addressing communication barriers and enhancing digital health infrastructure are essential for maximizing their effectiveness.